The Tobak Tradition in Kuta Jungak Village: Islamic Acculturation, Symbolic Meanings, and Social Functions in Pakpak Bharat Regency - Perjanggut Emas Padang; Muaz Tanjung (Mahesa Research Center (PT. Mahesa Global Publishing), 2026)
This study examines the historical development, contemporary practice, and symbolic meanings of the tolak bala tradition in Kuta Jungak Village, Pakpak Bharat Regency. The research explores how the tradition evolved, how it is implemented today, and how its meanings are interpreted amid socio-cultural change. Using a qualitative ethnographic approach, data were collected through in-depth interviews, documentation, and literature review, and analyzed through data reduction, presentation, and conclusion drawing. The findings show that the tradition originated from indigenous beliefs and later underwent Islamization, integrating Islamic prayers with local cultural symbols within the Sulang Silima kinship system. The ritual functions as a spiritual safeguard, a medium of social solidarity, and a marker of cultural identity. Its decline is associated with modernization, changing religious perspectives, weakening traditional authority, and reduced youth participation. The study concludes that the tolak bala tradition demonstrates the coexistence of Islamic acculturation and local wisdom while facing significant challenges from contemporary social transformation.